A Comparative Analysis of Knife and Firearm Homicides in the United States - Harms, Joshua (Journal of interpersonal violence, 2022)
In the United States of America firearms are the most common weapons used to commit homicide. This has led the public, academics, media, and policy makers to largely neglect other means of homicide. The second most common weapon used in the commission of a homicide in the USA are knives. On average more than 1,500 people are murdered with a knife each year in the USA. Little attention in the USA is focused on knife violence. However, the same is not true across the globe. After reviewing an international selection of literature, the current study aims to analyze both the victims and offenders of knife homicide in the USA by comparing them to the offenders and victims of firearm homicide. This was accomplished by analyzing data from the Supplementary Homicide Reports from 2014 to 2016. Comparisons between firearm and knife homicides included victim and offender demographics, as well as the relationship between the victim and offender. Bivariate and multivariate analysis are used to show that the victims and offenders of knife homicides are a significantly different group from the victims and offenders of firearm homicide. In the USA victims and offenders of knife violence are more likely to be female, less likely to be minorities, and are significantly older than firearm victims and offenders. The victim and offender in the case of a knife homicide are also significantly more likely to be closely related to one another. Unlike many other countries, in the USA the problem of knife violence appears much more similar to domestic violence than the typical street crime involving firearms. Because of this, knife homicides should not be approached with the same theoretical framework as firearm homicide. Additionally, the policies needed to effectively counter this problem will be different from those intended to deter firearm homicide.